Penerapan Bisnis Islami bagi Pengusaha Muslim di Pasar Besar Kota Malang - Rahmatullah, Rizqi; Hidayati, Nur; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The aims of this research are: 1) To describe and analyze application of Islamic business to Muslim entrepreneur in Pasar Besar Malang City, and 2) To describe and analyze the behavior of Muslim entrepreneur in Pasar Besar Malang City in running a business based on Islamic business principles. Methods of data collection is done by means of interviews, observation, and documentation. Based on the results of the research and discussion, it shows that Muslim entrepreneur in the Big. The entrepreneur's strategy is to identify community needs. Every shop is required to comply with regulations with legal ownership status under the auspices of the state and religion. The ethics of entrepreneur is that they do not raise prices and monopolize the market. Entrepreneur consistently open their shops at predetermined hours and close in the afternoon. As for the behavior of Muslim entrepreneur in Pasar Besar in doing business, namely satisfying customers, having openness, not deceiving or fooling customers, mutual help, and preaching by trading. This proves that doing business using the Islamic way is able to stabilize market conditions in the era of the onslaught of the capitalist economic system which is destroying the market. Keywords: Islamic business, Entrepreneur behavior, Muslim entrepreneur.